Ganglioneuroma of the neck: A case report - Ilknur Haberal Can; Yunus Kantekin; Betul Aytekin; Serdar Yanik; Kivanc Atilgan (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Objectives: An unusual left parapharyngeal ganglioneuroma case was discussed in the context of diagnostic difficulties, surgical tricks and Horner syndrome as a main surgical complication. Methods: The patient presented with a painless neck mass. Fine needle aspiration did not give any clue regarding diagnosis. The mass was removed totally by a challenging surgery.  Results: Histopathology revealed ganglioneuroma. Horner syndrome occurred after surgery. Conclusion: Due to the scarcity of ganglioneuromas and the lack of specific signs and symptoms, it is often difficult to reach a definitive diagnosis prior to pathological examination. Ganglioneuromas should be considered in differential diagnosis of cervical neck masses located medial to main neurovascular structures. The patients should be warned of the possible complication of Horner syndrome.